Growth promotion of some lactic acid bacteria by crude extract of Spirogyra sp.,Cladophora sp., Caulerpa lentillifera and Caulerpa corynephora - U. Chadseesuwan; S. Puthong; Pawinee Deetae (Food Research, 2021)
The aim of this research was to evaluate the growth promotion of two freshwater macroalgae (Spirogyra sp., Cladophora sp.) and two saltwater macroalgae (Caulerpa lentillifera and Caulerpa corynephora) crude extracts to some lactic acid bacteria using in vitro fermentation. Total soluble carbohydrates of macroalgae were obtained after extraction with 75oC of water for 1 hr. The concentration of total sugar and reducing sugar were 0.764 and 0.197 mg/g in Spirogyra sp., 0.368 and 0.082 mg/g in Cladophora sp., 0.484 and 0.055 mg/g in C. lentillifera, and 0.253 and 0.037 mg/g in C. corynephora, respectively. Degree of polymerization (DP) that refers to the size of oligosaccharide, were 3.8, 4.5, 8.8 and 6.8, respectively. The prebiotic activity was assessed by the change of the bacterial population. Crude extracts from macroalgae were tested for growth stimulation effect on lactic acid bacteria, Lactobacillus plantarum TISTR862 and Escherichia coli TISTR073. Results demonstrated that the population of L. plantarum TISTR862 and E. coli TISTR073 were higher in crude extracts from freshwater than saltwater macroalgae. The prebiotic activity score was calculated based on the change of growth in probiotic and pathogen after 24 hrs of incubation time. The highest score was obtained from C. corynephora extracts (1.10) follow by C. lentillifera extracts (0.77), Cladophora sp. extracts (0.173) and Spirogyra sp. extracts (0.07). In comparison with commercial culture (Lactobacillus casei, Lactobacillus lactis, Streptococcus thermophilus and Bifidobacterium), the addition of 3.5% C. lentillifera extracts resulted as prebiotic activity score value as 3.5% FOS. Preliminary study demonstrated that crude extract of C. lentillifera could be a prebiotic substance
Keywords: Seaweed-derived Bioactive Compounds; Food Industry and Aquatic Biology; Food and Agricultural Sciences